Una novela-testimonio dominicana sobre la dictadura de Trujillo : El Masacre se pasa a pie de Freddy Prestol Castillo - Lauro Capdevila (Amnis)
The novel El Masacre se pasa a pie by Freddy Prestol Castillo became a best-seller as soon as it was published in 1973 and was quickly regarded as a major national text. It is now being studied in dominican secondary schools. In this testimony-novel, to use the term coined by Miguel Barnet, the author reports in the first person the massacre of some 12 000 to 20 000 supposedly Haitians by Trujillo's henchmen in 1937. The event stands as one of the highlights during the dictatorship, and reveals its racist nature as well as the extreme violence displayed by the state against the population. It tries to assert the (historical ?) truth, against the lies of the official propaganda. Nurtured by a will of authenticity, the novel presents the upheavals which the Dominicans underwent during this dictatorial regime in a dynamic and synthetic way. In this book, literature proves to be an efficient way to restore the memory of the nation in order to rebuild it.